The effects of human care on the blowhole and gut microbiotas of two cohabiting dolphin species based on a year-round surveillance - Wan, Xiaoling; Li, Jia; Tian, Renmao; McLaughlin, Richard William; Hao, Yujiang; Wu, Junyi; Wang, Zhengyang; Fan, Fei; Wang, Ding; Zheng, Jinsong (Frontiers in Marine Science, 2022)
Understanding the effects of human care on the dynamics of the host-associated microbiota is critical for the health management of dolphins living in an aquarium. Yet this aspect remains relatively unexplored. Here, by utilizing 16S rRNA gene sequencing, we profiled the blowhole and gut bacterial communities of two bottlenose dolphins (Tursiops truncatus) and a Chinese white dolphin (Sousa chinensis) reared in the same indoor pool, based on year-round surveillance. In addition, we compared these dolphin microbiotas with those previously published datasets from wild dolphins. Our results showed that both the blowhole and the gut of the two dolphin species under human care shared a more similar microbiome than members of the same dolphin species across different habitats (human care vs wild). However, the effects of human care on the dolphin microbiome from the two body sites varied. In the aquarium, bacterial alpha diversities differed significantly between the two body sites, and the seasonal stability of the bacterial community was more evident in the gut than in the blowhole. Additionally, the blowhole bacterial composition and the predicted functional capacity from the two dolphin species showed differences and were less convergent than their gut microbiota over a decade-long cohabitation. Further analyses showed that heterogeneous and homogeneous selections (i.e., deterministic processes) contributed more to the blowhole than to the gut bacterial communities, while a dispersal limitation (i.e., a stochastic process) was more important for the gut microbiota. The present study provides the first comparative evidence that the gut microbiota may be more plastic in response to the human care environment than the blowhole microbiota. This improves our understanding of dolphin health management under human care and helps to predict their microbial responses to environmental changes.